Complete mesocolic excision in right‐sided colon cancer does not increase severe short‐term postoperative adverse events. (2nd May 2018) - Bernhoff, R.; Sjövall, A.; Buchli, C.; Granath, F.; Holm, T.; Martling, A.
Abstract: Aim: The aim was to assess whether complete mesocolic excision (CME) in patients with right‐sided colon cancer is related to short‐term mortality or postoperative adverse events requiring reoperation. The complete mobilization of an integral mesocolon and central ligation of blood vessels are essential steps in CME surgery. The resultant specimen, with an intact mesocolic fascia and a high number of harvested lymph nodes, is believed to be oncologically favourable. However, it has been suggested that CME surgery may increase the risk of intra‐operative severe adverse events, due to exposure of vital retroperitoneal organs and large blood vessels. Method: In a population‐based, nested case–control study, all residents in the Stockholm County operated for right‐sided colon cancer from 2004 until 2012 were identified from the Swedish Colorectal Cancer Registry. Patients who died within 90 days after surgery or were reoperated within 30 days after surgery, or during the index hospital stay, were defined as cases. Two controls per case were randomly sampled and individually matched for age, sex, TNM stage and emergency vs elective surgery. Exposure status (CME surgery) was assessed from original surgical reports. Results: The estimated proportion of CME surgery was 14.8% (35 of 236) for cases and 19.5% (92 of 473) for controls. The unadjusted OR for short‐term mortality or reoperation after CME surgery was 0.72 (95% CI: 0.47–1.10; P  =   0.15). The ORs were lower in the late part of the study (0.51; 95% CI: 0.26–1.01) and in high volume hospitals (0.61, 95% CI: 0.35–1.06). Conclusions: The present study does not indicate that CME surgery is associated with an increased risk of severe adverse events such as 90‐day mortality or reoperation.